Fatigue life assessment in lateral support element of a magnet for nuclear fusion experiment "Wendelstein 7-X". (1st June 2017) - Giannella, V.; Fellinger, J.; Perrella, M.; Citarella, R.
Highlights: A FEM-DBEM approach is used for crack-growth simulation in components undergoing complex load spectra. The adopted approach is based on the superposition principle applied to solve a LEFM problem. Growth rate and crack shape are provided and the component fatigue life is forecasted. Reduced runtimes of the proposed approach are highlighted. Accuracy and versatility of the adopted approach are highlighted. Abstract: Wendelstein 7-X (W7X), a nuclear fusion experiment of modular stellarator type, started operation in 2015 and will be upgraded with a water cooled first wall for steady state operation in 2020. A hot hydrogen plasma of ultra-low density is confined in a plasma vessel by an electromagnetic field generated by specially shaped superconducting coils. Such coils, embedded in a cryostat working at 4 K, are kept by a central support ring and joined together by welded lateral support elements (LSEs). In this paper, a coupled FEM-DBEM (Dual BEM) submodelling approach is adopted for crack-growth simulations of the cracks detected in LSEs and driven by a fatigue load spectra. A global analysis on one fifth of the fivefold symmetric magnet system is performed by FEM, whereas the submodelling approach is adopted to solve the crack propagation by DBEM. In particular, the adopted approach is based on the application of the superposition principle to solve a LEFM problem: the only boundary conditions for the DBEM submodel consist of tractions, calculated by the FEM global analysis and applied to the crack faces in the local submodel. The obtained speed of crack advance and crack kinking are compared with literature results to highlight the accuracy of the proposed approach together with inherent computational advantages.